Basal Exposure Therapy: A New Approach for Treatment-Resistant Patients with Severe and Composite Mental Disorders - Heggdal, Didrik; Fosse, Roar; Hammer, Jan (Frontiers in Psychiatry, 2016)
New treatment approaches are needed for patients with severe and composite mental disorders who appear resistant to conventional treatments. Such treatment resistant patients often have diagnoses of psychotic or bipolar disorders or severe personality disorders and comorbid conditions. Here we evaluate Basal Exposure Therapy (BET), a novel ward-integrated psychotherapeutic approach for these patients. Central to BET is the conceptualization of undifferentiated existential fear as basic to the patients’ problem, exposure to this fear, and the therapeutic platform Complementary External Regulation (CER) which integrates and governs the totality of interventions throughout the treatment process. BET is administered at a locked-door ward with six patient beds and 13.5 full time employees, including a psychiatrist and two psychologists. Thirty-eight patients who had completed BET were included, all but two being female, mean age 29.9 years. Fourteen patients had a diagnosis of schizophrenia or schizoaffective disorder (F20/25), eight had bipolar disorder or recurrent depressive disorder (F31/33), eight had diagnoses in the F40-49 domain (anxiety, stress, dissociation), five were diagnosed with emotionally unstable personality disorder (F60.3), and three patients had other diagnoses. Twenty of the patients (53%) had more than one ICD-10 diagnosis. Average treatment time in BET was 13 months, ranging from 2 to 72 months. Time-series data show significant improvements in symptoms and functioning from enrolment to discharge, with effect sizes at 0.76 for the Dissociation Experience Scale, 0.93 for the Brief Symptom Inventory, 1.47 for the Avoidance and Action Questionnaire, and 1.42 and 1.56, respectively for the functioning and symptom subscales of the Global Assessment of Functioning Scale. In addition, the patients used significantly less antiepileptic, antipsychotic, anxiolytic and antidepressant medications at discharge than at treatment enrolment. Patient improvement across treatment was associated with each of the successful completions of the exposure component of BET, with positive changes in psychological flexibility as measured with the Avoidance and Action Questionnaire, with high symptom levels and low levels of functioning at treatment start, and with the duration of time in BET. The findings indicate that BET may be a promising inpatient psychotherapeutic approach for previously treatment resistant patients with severe and comorbid conditions.